Integrative analysis of grapevine (Vitis vinifera L) transcriptome reveals regulatory network for Chardonnay quality formation - Fu, Guangqing; Ren, Yanhua; Kang, Jun; Wang, Bo; Zhang, Junxiang; Fang, Jinggui; Wu, Weimin (Frontiers in Nutrition, 2023)
Anthocyanins, total phenols, soluble sugar and fruit shape plays a significant role in determining the distinct fruit quality and customer preference. However, for the majority of fruit species, little is known about the transcriptomics and underlying regulatory networks that control the generation of overall quality during fruit growth and ripening. This study incorporated the quality-related transcriptome data from 6 ecological zones across 3 fruit development and maturity phases of Chardonnay cultivars. With the help of this dataset, we were able to build a complex regulatory network that may be used to identify important structural genes and transcription factors that control the anthocyanins, total phenols, soluble sugars and fruit shape in grapes. Overall, our findings set the groundwork to improve grape quality in addition to offering novel views on quality control during grape development and ripening.